Taxonomy of Levels of Sensing, Smart and Sustainable Products to support New Product Development. Issue 13 (2019) - Miranda, J.; Ponce, P.; Molina, J.M.; Molina, A.
Abstract: Nowadays, there is a tendency to provide products not only with high sensing and smart capacities and capabilities but also with high sustainable impact considering social, economic and environmental factors. Therefore, companies must offer products that can be competitive in the market and solve social problems through the use of emerging technologies and practices that allow high customisation and better performance of products. Accordingly, the sensing, smart and sustainable product 'S 3 Product' concept has emerged to define these types of products. In this work, a taxonomy of levels of S 3 Products to support New Product Development (NPD) is presented. Thus, the information generated by using the proposed taxonomy will support the design process and obtain an early identification of the value proposition of products to be developed.